Analysis of The Level of Maximal Oxygen Uptake (Vo2​Max) Ability in Football Extracurricular Students of MTs Bahrul Ulum, Rokan Hulu Regency - Aprizal Kurniawan; Ardo Yulpiko Putra; Resdianto Resdianto (Universitas Cahaya Prima, 2026)
VO₂Max is an important indicator of cardiorespiratory fitness that plays a significant role in supporting performance in football. This study employed a descriptive quantitative method with a survey design. The population of this study consisted of all grade VIII students who participated in the football extracurricular activity at MTs Bahrul Ulum, totaling 20 students. The sampling technique used was total sampling, meaning that all members of the population were included as research participants. The instrument used to measure VO₂Max was the Multi-Stage Fitness Test (MFT), also known as the Beep Test. The test results were analyzed using descriptive statistics and frequency distribution. The results showed that the VO₂Max ability of students participating in the football extracurricular activity at MTs Bahrul Ulum was generally at a low level. The lowest recorded VO₂Max value was 24.00 and the highest was 42.90. The average (mean) value was 31.87 with a standard deviation of 5.74. Based on the frequency distribution, the majority of students were categorized as Poor and Fair. Specifically, 50% of students (10 individuals) were in the Poor category and 30% of students (6 individuals) were in the Fair category. The study concluded that the VO₂Max capacity of MTs Bahrul Ulum football extracurricular students is at a low level, indicating that their cardiorespiratory fitness still needs improvement to achieve optimal performance and long-term health benefits. Therefore, it is recommended that more structured and specific training programs be implemented to improve VO₂Max.